The cybersecurity guide to governance, risk, and compliance - Edwards, Jason; Weaver, Griffin (2024)
"Cyber Security Governance & Risk Management is the monitoring of compliance with agreed cyber security policies and the assessment and management of relevant risks. Cybersecurity is a critical concern for modern businesses, and understanding how to navigate it is vital"--
Includes index.
Keywords: Business enterprises -- Computer networks -- Security measures; Computer security; Computer crimes -- Prevention